2020
DOI: 10.1097/fjc.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Attenuates Cholesterol Accumulation in Macrophage Foam Cells by Suppressing AP-1 Activity and Activation of the Nrf2/HO-1 Pathway

Abstract: Atherosclerosis is a chronic inflammation condition resulting from the interaction between lipoproteins, monocyte-derived macrophages, T lymphocytes, and other cellular elements in the arterial wall. Macrophage-derived foam cells play a key role in both early and advanced stage of atherosclerosis. Previous studies have shown that berberine could inhibit foam cell formation and prevent experimental atherosclerosis. However, its underlying molecular mechanisms have not been fully clarified. In this study, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…Indeed, as A1542 activates MAPK/ERK signaling, many of these genes (including TNF, FOS, JUN, FOSB and IER2) are known downstream of this kinase pathway [ 31 , 32 ]. Among these genes, AP1 (FOS + JUN) activation was previously implicated in cholesterol biosynthesis [ 33 , 34 ]. We then examined the effect of the AP1 inhibitor Tan IIA [ 35 ] on expression of the cholesterol genes induced by A1542.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as A1542 activates MAPK/ERK signaling, many of these genes (including TNF, FOS, JUN, FOSB and IER2) are known downstream of this kinase pathway [ 31 , 32 ]. Among these genes, AP1 (FOS + JUN) activation was previously implicated in cholesterol biosynthesis [ 33 , 34 ]. We then examined the effect of the AP1 inhibitor Tan IIA [ 35 ] on expression of the cholesterol genes induced by A1542.…”
Section: Resultsmentioning
confidence: 99%
“…The role of AP1 in survival vs apoptosis is now attributed to the cellular context and extracellular stimulus [ 43 ]. AP1 activation was also implicated in cholesterol biosynthesis [ 33 , 34 ], although its role in lipid induction and cell survival is still unknown. Here we showed that pharmacological inhibition of AP1 blocked the induction of cholesterol genes by A1542, providing another pathway for lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 mediates the upregulation of CD36 expression and has been reported to play a key role in lipid metabolism in macrophages and within the aorta. [ 127 , 128 ] FGF21 deficiency upregulated Nrf2, CD36, and FATP expression in cardiomyocytes, whereas FGF21 supplementation strongly suppressed their expression levels. [ 113 , 123 , 124 ] Additionally, cardiac dysfunction in patients with DM is partly attributed to the accumulation of lipid droplets in cardiomyocytes.…”
Section: Effect Of Fgf21 On Cmpmentioning
confidence: 99%
“…Multiple lines of evidence suggest the Nrf2 is a master transcriptional regulator of various antioxidant and cytoprotective genes. In various preclinical ischemia and reperfusion experimental models, it has been demonstrated the downregulation of Nrf2 and associated antioxidant genes expression in cardiac tissue (Silva‐Palacios et al, 2019; Yang, Ding, et al, 2020; Yang, Liu, et al, 2020; Yang, Mao, et al, 2020; Zhao et al, 2020; Zhao, Chen, Wang, & Cai, 2020; Zheng et al, 2020). Recently, Wang et al (2020) demonstrated that the silensing of the gene, Nrf2 or HO‐1 reduces the viability of neonatal cardiomyocytes isolated from neonatal mice following hypoxia/reoxygenation.…”
Section: Herbal Nrf2 Activator and Cardiovascular Diseasesmentioning
confidence: 99%